Transformasi Manajemen Pendidikan Islam di Era Globalisasi: Tantangan dan Peluang - Wiwi Uswatiyah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to analyze the transformation of Islamic education management in the era of globalization, focusing on the challenges and opportunities faced in maintaining the relevance and quality of Islamic education. In the context of globalization, Islamic education faces pressure to adapt to technological advances, social changes, and global standards, which necessitates a dynamic and innovative management approach. This research employs a qualitative-descriptive method through literature review, interviews, and field observations in Islamic educational institutions in Indonesia. The academic debate in this research includes diverse perspectives on integrating local values with global demands, as well as the dilemma between modernization and the preservation of tradition. Some advocate for modernization as an effort to enhance the competitiveness of Islamic education, while others are concerned that modernization may erode fundamental Islamic values. This study finds that the transformation of Islamic education management in the globalization era has the potential to improve the effectiveness and efficiency of educational institutions, particularly through the application of information technology and the development of a more inclusive and contextual curriculum. However, this process requires Islamic educational institutions to be more adaptive, while maintaining the essence of religious teachings. The findings of this research are expected to contribute to the development of policies that support sustainable Islamic education that is relevant to the times while remaining rooted in Islamic values.